2015
DOI: 10.5588/ijtld.14.0499
|View full text |Cite
|
Sign up to set email alerts
|

Health care-seeking behaviour among people with cough in Tanzania: findings from a tuberculosis prevalence survey

Abstract: A third of the persons with cough symptoms consistent with TB had sought health care. About 42% sought care in sites with TB diagnostic capacity, but most did not undergo TB diagnostic procedures, precluding a timely diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 24 publications
(29 reference statements)
4
35
0
Order By: Relevance
“…Our findings affirm the findings of the First National Tuberculosis Prevalence Survey in Tanzania where prevalence was higher in males than in females 13 . The findings are consistent with results from China 14 and India 15 as well as studies in Ethiopia and Brazil where males were reported to have an increased risk of TB even in HIV-infected population 16,17 .…”
Section: Discussionsupporting
confidence: 82%
“…Our findings affirm the findings of the First National Tuberculosis Prevalence Survey in Tanzania where prevalence was higher in males than in females 13 . The findings are consistent with results from China 14 and India 15 as well as studies in Ethiopia and Brazil where males were reported to have an increased risk of TB even in HIV-infected population 16,17 .…”
Section: Discussionsupporting
confidence: 82%
“…In almost half of these cases, the disease remains undiagnosed until death [2]. TB patients are often diagnosed at the later stages of the disease, due to health-seeking behaviour, inappropriate diagnostic investigations requested by health care providers, and limited diagnostic capacities at health care facilities (HCFs) [3, 4]. Patients experiencing TB symptoms may initially seek relief by using self-prescribed medication or by consulting a health care provider who does not request TB investigations despite repeated visits [5].…”
Section: Introductionmentioning
confidence: 99%
“…Delay in seeking care, therefore, promotes continued TB transmission [9]. The complex pathway to care, from the onset of symptoms to diagnosis and treatment, may result in delays in seeking care and contribute to patient morbidity and mortality [4, 10]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It particularly infects lungs, although other organ infections are also observed. Main symptoms of Tuberculosis are continuous fever and cough for more than two weeks [2]. More than 8.5 million new cases of TB were recorded in 2010 of which more than 95% were identified in developing countries and 65% in Asia [3].…”
Section: Introductionmentioning
confidence: 99%